2017
DOI: 10.7717/peerj.3454
|View full text |Cite
|
Sign up to set email alerts
|

Ecophylogeny of the endospheric root fungal microbiome of co-occurring Agrostis stolonifera

Abstract: BackgroundWithin the root endosphere, fungi are known to be important for plant nutrition and resistance to stresses. However, description and understanding of the rules governing community assembly in the fungal fraction of the plant microbiome remains scarce.MethodsWe used an innovative DNA- and RNA-based analysis of co-extracted nucleic acids to reveal the complexity of the fungal community colonizing the roots of an Agrostis stolonifera population. The normalized RNA/DNA ratio, designated the ‘mean express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 59 publications
1
49
0
1
Order By: Relevance
“…The roots were separated from the rest of the plant, washed with a stringent detergent solution (Triton X100, 1% V/V), then rinsed with ultra‐pure water before storage at −80°C and subsequent analysis of the root endosphere compartment (e.g. Lê Van et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The roots were separated from the rest of the plant, washed with a stringent detergent solution (Triton X100, 1% V/V), then rinsed with ultra‐pure water before storage at −80°C and subsequent analysis of the root endosphere compartment (e.g. Lê Van et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The sequence production and trimming strategy have been published previously (e.g. Ben Maamar et al, ; Ciobanu et al, ; Lê Van et al, ). Sequences shorter than 300 bp in length, with homopolymers longer than 8 bp or with ambiguous nucleotides, were removed from the dataset.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy root fragments were selected for being representative of the different parts of the rooting system. After this cleaning step, only root‐adhering epiphytic and endophytic microorganisms were still present with the roots (Lê Van et al ). Cleaned roots of each sample were ground to powder under liquid nitrogen using a pestle and mortar.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding the assembly rules of plant microbiota is a central question of plant biology because of the tremendous ecological functions provided by symbiotic microorganisms to plants (Davison et al , Lekberg and Waller ). Next‐generation sequencing approaches have demonstrated that the microbiota of plants is composed of a large diversity of microorganisms, including bacteria (Lundberg et al , Bulgarelli et al ), archaea (Edwards et al , Vannier et al ), and fungi (Vandenkoornhuyse et al , Coleman‐Derr et al , Lê Van et al ). An increasing number of studies suggest that the identity of the host‐plant species (Vandenkoornhuyse et al , Martinez‐Garcia and Pugnaire , Yang et al ) and to some extent, its genotype (Bodenhausen et al , Edwards et al ) condition the associated microbiota through the preferential recruitment of particular fungi.…”
Section: Introductionmentioning
confidence: 99%